Blind equalization in the presence of co-channel interference based on higher-order statistics - Wang, Guohua (2020)
An improved blind channel equalization method is proposed based on the generalized eigenvector algorithm (GEA) in this paper. This new method can blindly equalize the desired signal in the presence of strong co-channel interference. The basic idea underlying the improved GEA method is that higher-order cumulants can be sensitive to frequency offset. By exploiting this property of higher-order statistics, blind equalizer can be designed to equalize the desired signal with known frequency offset while suppressing the interference with a different frequency offset. Simulation results are shown to demonstrate the effectiveness of the proposed method.